Reducing frost heave and salt migration in saline soil foundations of channels in seasonal frozen regions using solidification - KANG Xinrui; LI Hongbo; TIAN Juncang; ZHANG Zhe; WANG Zi (Guan'gai paishui xuebao)
【Objective】Saline soils in seasonal frozen regions are often used as channel foundations but are prone to frost heave and salt migration, which can compromise structural stability. The objective of this paper is to investigate the efficacy of soil solidification in improving frost resistance and mitigating salt migration, and provide insights for improving engineering design in cold regions. 【Method】Freeze -thaw cycle tests were conducted on saline soil with and without solidification in laboratory. There were five test sets, with the compaction coefficient varying from 0.855 to 0.952 and soil moisture content ranging from 10% to 18%. Key parameters, including frost heave force, frost heave volume, and salt migration were measured during the experiment.【Result】① Both solidified and non-solidified saline soils exhibited significant fluctuation in the frost heave force for temperature in the range of -10 to 0 ℃. Solidification reduced the frost heave force by up to 65.0% compared to non-solidified soil. ②Solidification reduced the frost heave volume by 41.8% at the same soil depth, compared with non-solidification. ③Salt migration decreased with increasing soil depth in both solidified and non-solidified soils. However, significantly slower migration was observed in solidified soils. ④ With the increase in compaction coefficient, the frost heave force, frost heave volume, and salt migration initially increased, followed by a decline, after the increase exceeded a threshold. 【Conclusion】Soil solidification significantly improved the frost resistance and reduced salt migration in saline soils. An empirical model was developed to estimate the maximum frost heave force and volume based on compaction coefficient and the number of freeze-thaw cycles, as well as salt migration as a function of soil depth. Our findings suggest that a compaction coefficient in the range of 0.85-0.90 is optimal for small-scale channel foundations, while a compaction coefficient exceeding 0.94 is recommended for medium to large-sized channels.